2022
DOI: 10.1155/2022/1395299
|View full text |Cite|
|
Sign up to set email alerts
|

Scutellarin Loaded on Ultradeformable Nanoliposome Scutellarin EDTMP (S-UNL-E) Promotes Osteogenesis in Osteoporotic Rats

Abstract: Scutellarin is known as a safe, effective, and low-cost traditional Chinese medicine and has a variety of biological activities. Studies reported that the scutellarin loaded on ultradeformable nanoliposome scutellarin EDTMP (S-UNL-E) could promote osteoblast differentiation and bone formation in vitro. However, its effect on promoting osteogenesis in vivo is still unclear. In this study, pharmacology network and transcriptome sequencing were used to screen the potential targets and pathways of scutellarin in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The wide range of pharmacological properties that SCU contains, including the ability to treat diseases and have protective benefits on the body, have been shown by contemporary pharmacological investigations. Its anti-tumor, glaucoma-improving, anti-depressive, and osteoporosis-preventive qualities are a few of these functions ( Lu et al, 2021 ; Zhu et al, 2021 ; Chen et al, 2022a ; Teng et al, 2022 ). Multiple benefits of SCU on cardiovascular illnesses include anti-myocardial fibrosis, protection of vascular endothelial function, attenuation of myocardial injury, and improvement of cardiac function ( Xu et al, 2020 ; Duan et al, 2021 ; Li et al, 2023b ; Sun et al, 2023 ).…”
Section: Scutellarinmentioning
confidence: 99%
“…The wide range of pharmacological properties that SCU contains, including the ability to treat diseases and have protective benefits on the body, have been shown by contemporary pharmacological investigations. Its anti-tumor, glaucoma-improving, anti-depressive, and osteoporosis-preventive qualities are a few of these functions ( Lu et al, 2021 ; Zhu et al, 2021 ; Chen et al, 2022a ; Teng et al, 2022 ). Multiple benefits of SCU on cardiovascular illnesses include anti-myocardial fibrosis, protection of vascular endothelial function, attenuation of myocardial injury, and improvement of cardiac function ( Xu et al, 2020 ; Duan et al, 2021 ; Li et al, 2023b ; Sun et al, 2023 ).…”
Section: Scutellarinmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%